1981
DOI: 10.1126/science.211.4477.16
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Agriculture of the Mount St. Helens Eruptions

Abstract: Ash from Mount St. Helens has fallen over a diverse agricultural area, with deposits of up to 30 kilograms per square meter. Crop losses in eastern Washington are estimated at about $100 million in 1980-about 7 percent of the normal crop value in the affected area and less than was expected initially. Production of wheat, potatoes, and apples will be normal or above normal because the favorable conditions for growth of these crops since the ashfall helped offset the losses. Alfalfa hay was severely lodged unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 6 publications
(7 reference statements)
2
72
0
2
Order By: Relevance
“…The chemical composition of dust, its particulate size, age of plants and deposition rate were studied intensively [19,21]. For example, cement kiln dust reduced 73% of the photosynthesis in green beans [22], while ash reduced up to 90% of the rate of photosynthesis of apple trees [23]. Nanos and Ilias [24] described the effects of cement dust, such as a reduced stomatal conductance and transpiration rate of olive trees.…”
mentioning
confidence: 99%
“…The chemical composition of dust, its particulate size, age of plants and deposition rate were studied intensively [19,21]. For example, cement kiln dust reduced 73% of the photosynthesis in green beans [22], while ash reduced up to 90% of the rate of photosynthesis of apple trees [23]. Nanos and Ilias [24] described the effects of cement dust, such as a reduced stomatal conductance and transpiration rate of olive trees.…”
mentioning
confidence: 99%
“…This tepha horizon is stratigraphically below the coarser tephra and we attribute it to the older eruptive event. All tephra horizons analysed had bulk densities less than 0.85 Mg m -3 with very low hydroscopic water holding capacities (>1500 kPa), which are typical for the porosity characteristics of recently deposited tephra Cook et al 1980).…”
Section: Soil Physical and Chemical Propertiesmentioning
confidence: 94%
“…The prediction of a threat continued until the year 2010. Experiments on the volcanic material showed that rice still thrived in the chemical and physical deficiencies of volcanic materials in Mount Pinatubo, with the application of nitrogen fertilizer [35]. The volcanic eruption of Mt.…”
Section: Resilience Sustainability and The Implication For Practicalmentioning
confidence: 99%